Longitudinal Variations of M. tuberculosis-Induced IFN-γ Responses in HIV-Negative Pregnant Women Exposed to Tuberculosis - Ranaivomanana, Paulo; Ratovoson, Rila; Razafimahatratra, Crisca; Razafimahefa, Arimanitra; Hoffmann, Jonathan; Herindrainy, Perlinot; Rakotonirina, Julio; Rakotosamimanana, Niaina (Frontiers in Immunology, 2021)
Introduction: Pregnancy triggers an alteration of the immune functions and increases the risk of developing the active tuberculosis (TB) symptoms in exposed women. The effect of pregnancy on the Mycobacterium tuberculosis-speciﬁc immune responses used for most of the TB immunodiagnostic assays is not well documented. Here we investigated the changes in the M. tuberculosis-speciﬁc IFN-γ production in age-matched pregnant and non-pregnant women according to their TB exposition status. Methods: We conducted a prospective cohort study of HIV-seronegative pregnant and non-pregnant women with compatible pulmonary TB symptoms addressed to TB healthcare facilities in Antananarivo, Madagascar. Active pulmonary TB was bacteriologically assessed with culture from sputum samples. Clinical data and blood samples were collected at inclusion and after six months of follow-up for each individual included. Whole blood samples were stimulated with QuantiFERON TB-Gold Plus (QFT-P) assay antigens. Plasma IFN-γ levels were then assessed by ELISA. Results: A total of 284 women were investigated for the study including 209 pregnant women without confirmed TB (pNTB), 24 pregnant women with confirmed active TB (pATB), 16 non-pregnant women with active TB (ATB) and 35 non-pregnant healthy donors (HC). At inclusion, IFN-γ responses are lower in the pregnant women compared to their age-matched non pregnant counterparts and independently of their TB status. Amongst the pregnant women, higher levels of M. tuberculosis-speciﬁc IFN-γ were observed in those exposed to TB, but with a lower magnitude in the active TB compared to the latently infected pregnant women (p<0.05 with TB1 and p<0.01 with TB2). After six months of follow-up, the M. tuberculosis-speciﬁc IFN-γ returns to their baseline levels except for the pregnant women treated for TB for which none of the QFT-P positive reversed to negative (0%, 0/10) at the end of their TB treatment. Conclusion: These results support the concept of specific immune priorities characterized by a concomitant reduction in inflammatory immunity during pregnancy and corroborate the important role of activating the M. tuberculosis-speciﬁc immune responses to control the infection when the pregnant women are exposed to the pathogen.